Problematika pravne ureditve Zoisovih štipendij - Pavliha, Gaja Ana (Pravnik, 2015)
The purpose of this article is to evaluate critically the modifications of legislation concerning the Zois scholarships, especially injustices affecting the scholarship holders entitled to scholarships in accordance with the previous law on scholarships. Disputable is particularly the regulation of transition period, which most likely contradicts the principle of equality and the principle of trust in law. There are also a few other problematic novelties enacted by the new law on scholarships.
Keywords: izobraževalna politika; pravna ureditev; Slovenia; Slovenija; štipendiranje; štipendisti; Zoisove štipendije